Gamma ray irradiation can reduce proteins in NR - Alex R; Abraham E K; Joseph Joy (Rubber Asia Margma, 2016)
An attempt is made to reduce protein content of natural rubber by exposure to different doses of gamma radiation. Exposure of natural rubber (NR) latex to low doses of y radiation results in partial degradation of proteins. By treating the y ray irradiated latex with protein hydrolysing enzyme, it is possible to further reduce the protein content of NR equivalent to that of deproteinised natural rubber (DPNR), along with raw rubber characteristics acceptable as per graded natural rubber. Generally, DPNR produced by enzymatic hydrolysis of proteins have a lower initial plasticity (P0) and lower plasticity retention index (PRI) while a combination of gamma ray exposure and enzyme treatment results in DPNR of high P0 and PRI. Exposure of creamed latex which is obtained from latex that is irradiated by low doses of y radiation and compounded with suitable sensitiser; to higher doses of gamma radiation results in radiation vulcanised natural rubber latex (RVNRL). Such RVNRL has an advantage that it is suitable to produced latex ased products with very low leachable proteins after suitable leaching operations, as Type 1 allergy has ben reported with latex products that have high amount of leachable proteins. On exposure of latex to varying doses of y radiation the following chemical changes are to take place (1) degradation of proteins (2) formation of micro gel that enhances green strength and initial plasticity of rubber (3) cross linking of rubber molecules inside the rubber particles. Most of the degraded proteins can be removed easily during further processing of latex. Exposure of NR latex to y radiation is a simple and less time consuming technique to produce deproteinised natural rubber with good raw rubber characteristics and radiation vulcanised natural rubber latex that can be used to produce latex products with very low leachable proteins.
Keywords: Deproteinisation; Gamma ray irradiation; Gel content; Initial plasticity; Natural rubber latex